Increased serum levels of lipogenic enzymes in patients with severe liver steatosis - Notarnicola, Maria (BioMed Central, 2012)
BACKGROUND: Lipid metabolism is altered in subjects with liver steatosis. FAS is a key enzyme in de novo lipogenesis and both FAS gene expression and enzymatic activity are primarily regulated by metabolic signals in the liver. Lipoprotein lipase (LPL), the rate-limiting enzyme for the hydrolysis of core triglycerides, plays a pivotal role in lipid metabolism. This study aims to investigate if circulating levels of FAS and LPL could be clinically associated with liver steatosis. METHODS: In this work, we present data obtained from a subsample of 94 subjects with liver steatosis enrolled by NUTRIEPA study, a nutritional trial in subjects with liver steatosis. Serum levels of FAS protein and LPL activity were evaluated by ELISA test and by a fluorescent method, respectively. The diagnosis and the degree of liver steatosis were based on laboratory and ecographic measurements. Statistical methods included Kruskal-Wallis analysis of variance and Wilcoxon signed-rank test, where appropriate. The χ(2) test has been performed to analyse categorical variables. RESULTS: The subjects with severe steatosis had significantly higher serum levels of FAS protein and LPL activity compared to subjects with mild and moderate liver steatosis. Moreover, a positive trend in serum levels of FAS expression from lower to higher degree of steatosis was also detected. CONCLUSIONS: We describe a relationship between human liver steatosis and elevated levels of circulating lipogenic enzymes. Increased serum levels of FAS expression and LPL activity could be considered a marker of severe liver steatosis.